BER reduction in signal receivers towards greening of digital communications. (1st January 2014) - Ahuja, Amit Kumar; Chakka, Ram; Krishna, P. Venkata
Bit-error-rate (BER) is an important efficacy-limiting factor in digital communications. Reducing bit-error-rate would give rise to many advantages. Transmission costs of digital signals would reduce since bandwidth requirement reduces. Also, transmission of signals at low SNR would become possible. The latter advantage adds to greening of today's communication technologies. In this paper, a special class of digital signals is considered. Improved methods are suggested for reducing the bit-error-rate at the receiver. Implementation of signal generation and recovery are done using MATLAB. The advantages are plotted in terms of bit-error-rate and bit-error-rate-reduction factor by comparing the performance with that of the conventional method.